Determinants of metabolic syndrome in people living with human immunodeficiency virus in Africa: a systematic review and meta-analysis - David, Emmanuel Agada; Olayanju, Olatunde Ayodeji; Sanusi, Kamaldeen Olalekan; Mabadeje, Oluseun Iyabode; Mshelia, Philemon Paul; Orabueze, Ibuchukwu; Kunle-Ope, Chioma Nneka; Ezenwosu, Ifeyinwa; Mamuda, Kasimu; Atinge, Sonnen; Adeniran, Adeoti Gbemisola; Akiode, Saheed Olatunbosun; et al. (Frontiers in Reproductive Health, 2025)
BackgroundMetabolic syndrome (MetS) among people living with HIV (PLHIV) is an emerging concern in Africa, but its underlying causes remain unclear. This study is a systematic review and meta-analysis of observational studies published between January 2000 and June 2025 to synthesize evidence on the determinants of MetS among PLHIV in Africa.MethodsPubMed, Web of Science, Scopus, and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases were searched for studies reporting determinants of MetS among PLHIV in Africa. Two reviewers independently screened and extracted data, and the risk of bias was assessed with the Newcastle-Ottawa Scale.ResultsThirty-six studies were included, while 23 were meta-analyzed. Female sex was strongly associated with MetS [Pooled odds ratios (PORs) = 2.86, 95% CI: 1.74–4.72], as was alcohol consumption (POR = 1.46, 95% CI: 1.04–2.03) and elevated BMI (>25 kg/m2) (POR = 4.27, 95% CI: 1.83–9.33). HIV-positive status showed significant effect (OR = 1.04, 95% CI: 1.01–1.09), while smoking (POR = 0.88, 95% CI: 0.48–2.70) and physical activity (POR = 0.98, 95% CI: 0.35–2.80) were not significantly associated. Substantial heterogeneity was observed for BMI, smoking, and physical activity.ConclusionFemale sex, alcohol consumption, and elevated BMI emerged as consistent determinants of MetS among PLHIV in Africa. These findings highlight the importance of proactively integrating, context-specific strategies for metabolic risk management into HIV care to address the rising burden of cardiometabolic disease in the region.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251066865, PROSPERO CRD420251066865.